ANALISIS RISIKO PRODUKSI DAN PENDAPATAN USAHATANI BAWANG MERAH VARIETAS TAJUK DAN MANJUNG DI KECAMATAN BANGGAE TIMUR, KABUPATEN MAJENE - Fitri Fitri; Suryani Dewi; Nadira Nadira (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Shallot is a superior commodity which has high economic and strategic values. To increase the income and welfare of farmers, the distric government of Majene through Agriculture, Livestock and Plantation Departmen encourages the development shallot farming tajuk dan manjung varieties. However, as is the case with agricultural commodities, The risk often faced by shallot farmers is production risk which is a variation of output caused by various factors. This study aims to know the feasibility and analyze the production risk and income of shallots. The method used in this study is quantitative method . The location is determined by purposive. Data obtained through interviews with 20 shallot farmers both tajuk and manjung varieties. The method used are revenue cost ratio and coefficient of variation (CV) analysis. The results showed that shallot farming of  tajuk variety more than profitable than manjung variety. Risk production and income shallot  farming of manjung variety higher than shallot farming of tajuk variety.